Private Urban Garden Satisfaction and Its Determinants in Quito, Ecuador - Cruz-Cárdenas, Jorge (2018)
Because of their importance to people, nature, and societies, domestic gardens have attracted increasing research interest. However, significant areas of interest remain unexplored, such as the variables that determine individuals’ satisfaction with their gardens. Our main goal was to address this gap. We surveyed 1,005 individuals with home gardens in Quito, Ecuador, to collect information on three groups of variables: (a) psychological and individual factors, (b) social and family aspects, and (c) garden characteristics. We used these groups of variables as predictors of satisfaction in a regression model (R2 = 0.242), with the first and third contributing the most to our understanding of satisfaction. In particular, people tended to be more satisfied with gardens composed of mostly native plants. In addition, individuals tended to be more satisfied if their motives for garden use were related to nature. In contrast, a high level of consumed resources negatively affected satisfaction. © 2018, © The Author(s) 2018.